Penggunaan Media Pembelajaran Film Pendek Dalam Mengulas Karya Fiksi Siswa Kelas VIII SMPN 5 Kota Jambi - Muhammad Afif Hibatullah; Nazurty Nazurty; Ade Bayu Saputra (Universitas Batanghari Jambi, 2026)
This study aims to describe the use of short film media in teaching students to review fictional works in Grade VIII at SMPN 5 Kota Jambi. The background of this research stems from students’ low reading interest and their difficulty in understanding fictional elements when learning relies solely on written texts. Short films were selected as learning media because they provide concrete visualizations of stories, are engaging, easy to access, and capable of improving students’ ability to analyze and evaluate fictional works. This research employed a descriptive qualitative approach, with data collected through classroom observations, interviews, and document analysis of students’ review assignments. Data were analyzed using the interactive model by Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that the use of short films enhances students’ activeness during the learning process, strengthens their understanding of themes, characters, plot, setting, and moral messages, and helps them produce more structured and coherent reviews. Students demonstrated higher responsiveness, enthusiasm, and comprehension when the material was presented through audiovisual media. However, the study also found that teachers need to manage class time more effectively and provide additional guidance to ensure that students focus not only on the viewing experience but also on deeper analytical processes. Overall, the use of short film media proves to be relevant and effective in supporting Indonesian language learning, particularly in teaching the skill of reviewing fictional works, and it offers a creative and contextual alternative learning method that can be applied in schools.